2016
DOI: 10.1038/srep30649
|View full text |Cite
|
Sign up to set email alerts
|

HCV derived from sera of HCV-infected patients induces pro-fibrotic effects in human primary fibroblasts by activating GLI2

Abstract: Hepatitis C virus (HCV) infection is a leading cause of liver fibrosis, especially in developing countries. The process is characterized by the excess accumulation of ECM that may lead, over time, to hepatic cirrhosis, liver failure and also to hepatocarcinoma. The direct role of HCV in promoting fibroblasts trans-differentiation into myofibroblasts, the major fibrogenic cells, has not been fully clarified. In this study, we found that HCV derived from HCV-infected patients infected and directly induced the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…HCV can directly infect human skin fibroblasts and induce the expression of pro-fibrotic proteins such as vimentin, collagen, and α-SMA by activating GLI2 (glioma-associated oncogene family zinc finger 2), which has been previously linked to organ fibrosis [53,54]. Since HSCs are considerably different from skin fibroblasts [55], this finding should also be confirmed in HSCs.…”
Section: Hcv-mediated Liver Fibrosismentioning
confidence: 91%
“…HCV can directly infect human skin fibroblasts and induce the expression of pro-fibrotic proteins such as vimentin, collagen, and α-SMA by activating GLI2 (glioma-associated oncogene family zinc finger 2), which has been previously linked to organ fibrosis [53,54]. Since HSCs are considerably different from skin fibroblasts [55], this finding should also be confirmed in HSCs.…”
Section: Hcv-mediated Liver Fibrosismentioning
confidence: 91%
“…Recently published literature describes Hh pathway inhibitors as the following three categories: inhibitors targeting Smo, including nature compound (cyclopamine) and synthetic small molecules (vismodegib, sonidegib, IPI-926, BMS-833923, PF-04449913, SANT1–4, Cur61414, MRT-10); strategies to target the upstream N-Shh ligand, including Robotniknin and anti-Shh 5E1; and inhibitors targeting the downstream transcription factors Gli1 and Gli2, including Darinaparsin, GANT-61/58, HPI-1, and Forskolin ( 90 ). Various in vivo and in vitro studies demonstrated that some of these Hh pathway inhibitors, such as vismodegib ( 91 ), sonidegib ( 92 ), Forskolin ( 93 ), GANT-61 ( 94 ), GANT-58 ( 95 ), and cyclopamine ( 96 ), are capable of inhibiting or reversing the progression of liver fibrosis. Moreover, modulating repair-related inflammation response during the liver injury and repair is one of the important mechanisms of action for anti-fibrotic effect of these Hh pathway inhibitors.…”
Section: Targeting Hh Signaling Pathway For Anti-fibrotic Therapy Thrmentioning
confidence: 99%
“…Autophagy is articulated in several steps that go from autophagosome formation and elongation to their degradation into the lysosomes. It is involved in a variety of cellular functions including cell death, survival and differentiation, depending on the cell types and on the extent to which the process is activated [18][19][20]. Autophagy upregulation may help cells to cope with increased demands induced by stressful conditions by degrading and eventually recycling misfolded and long-lived proteins and damaged organelles [21].…”
Section: Introductionmentioning
confidence: 99%